Experimental Study on Wind Loading Characteristics of Trains under Stationary Tornado-like Vortices - Peng Li; Bo Li; Xiaoyu Han; Yuji Tian; Ruoqi Li (Buildings, 2022)
The risk of trains being hit by tornadoes in China continues to increase due to the increasing density of railway lines and the shortening of the train departure intervals and the increasing probability of extreme weather phenomena caused by global climate change. If a train is hit by a tornado, it will cause huge casualties and economic losses, so it is necessary to investigate the tornado-induced effects on trains. A series of rigid-model wind pressure measurement tests on a train car under tornado wind loading were conducted using a tornado-vortex simulator, in order to determine the effects of the distance between the train car and the tornado’s center, the swirl ratio of a tornado-like vortex, and the ground roughness on the wind pressure distributions and wind load characteristics on trains. Apparent discrepancies were observed between tornado-induced wind loading and lateral wind loading obtained from conventional boundary-layer wind tunnel tests. The wind pressure and wind load on the car surface are mainly affected by the combined effects of the aerodynamic flow-structure interaction and the pressure drop accompanying the tornado within 1.5 times the vortex core’s radius, and the impact of tornado-like vortices on the train car is almost negligible as the distance from the train car to the tornado’s center exceeds three times vortex core’s radius. The variation trend of mean/fluctuating pressure coefficients is generally consistent. Large values of fluctuating pressure exist mainly on the top and side surfaces of the train car, especially the side surface proximal to the tornado’s center. The most unfavorable mean sectional side force coefficients were found when the train car is located in the tornado’s core and the largest lift force coefficients at the tornado’s center. The overall side force coefficients peaked when the train car is located at a distance of 1.5 times the tornado’s core radius, whereas the largest lift force coefficients were found when the train car was located at the tornado’s center. The overall distribution patterns of the wind force coefficients of the car under different swirl ratios and ground roughness levels are basically the same. The peak aerodynamic force value increases with increasing swirl ratio, and it decreases as ground roughness increases.